2020
DOI: 10.1590/s1678-9946202062042
|View full text |Cite
|
Sign up to set email alerts
|

Atypical clinical presentation of an Arthroderma gypseum infection in a renal transplant recipient

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…When immunity is weakened, deep infection by dermatophytes leads to infiltration of the skin and subcutaneous tissue, and causes lesions of the lymph nodes, internal organs, and central nervous system [ 9 ]. Walter et al [ 10 ] reported a case of granulation tissue in the ankle joint following an M. gypseum deep infection in a renal transplant recipient. However, knowledge gaps surrounding the immune system response to M. gypseum pose barriers to the comprehensive understanding of this infection.…”
Section: Introductionmentioning
confidence: 99%
“…When immunity is weakened, deep infection by dermatophytes leads to infiltration of the skin and subcutaneous tissue, and causes lesions of the lymph nodes, internal organs, and central nervous system [ 9 ]. Walter et al [ 10 ] reported a case of granulation tissue in the ankle joint following an M. gypseum deep infection in a renal transplant recipient. However, knowledge gaps surrounding the immune system response to M. gypseum pose barriers to the comprehensive understanding of this infection.…”
Section: Introductionmentioning
confidence: 99%